The Design of Space Based on Architectural Geometry - Wasilah, Wasilah; ., . (International Journal of Engineering and Technology, 2019)
The aim of expressional space is to facilitate the society to indulge their hobby and talent autodidactically. The space for expression in Makassar City is necessary for the mural artist and the youngsters who have a hobby to play a skateboard. Their talent is not seriously attention from the government and creates negative attitude because there is no a space to accommodate their activity. This paper presents a design idea of expressional space with the implementation of the architectural geometry. The architectural geometry design principle is based on simple geometry form application as a realization of a form from the space. An experience of the space for the user realizes by the relationship between the space and the interaction with the environment through geometry and form processing as the basis of the creation process in the architectural works. Content analysis method providing a landscape layout and transformation of form and building mass in form of the implementation of architectural geometry principles. The principles are pure geometry, the composition of geometry, direction wall, and opening for the transformation process of expressional space form to produce and increases an aesthetic value of the environment.Â Â